Stigma Masyarakat Terhadap ODHA Di Kelurahan Cipondoh - Siti Latipah; Shieva Nur Azizah Ahmad (Utan Kayu Publishing, 2022)
Stigma is a social problem that is unique to people living with HIV/AIDS. Living with HIV/AIDS is not an easy thing. There is a risk of discrimination in various social circles of PLWHA. The aim of community service is to increase public knowledge about the Social Interaction of People with Hiv/Aids (PLHAs) in Reducing Stigma. The implementation of community service is carried out through several stages, namely the preparation stage, implementation stage, and evaluation stage. The results of community service show that the relationship of family attitude factors to the stigma of PLWHA is significant with a p value of 0.006. Community service was carried out to 74 participants with the majority being women aged over 45 years. Factors that influence the stigma of PLWHA in Cipondoh Village are the attitude of the family towards PLWHA and the respondent's perception of PLWHA. It is necessary to provide complete information on HIV/AIDS to the community to provide an understanding that can change individual and community perceptions, including families, neighbors, and community leaders about PLWHA. Abstrak: Stigma sebagai sebuah permasalahan sosial yang khas pada orang dengan HIV/AIDS. Hidup dengan terjangkit HIV/AIDS bukanlah suatu perkara yang mudah. Ada resiko diskriminasi di berbagai lingkungan sosial ODHA. Tujuan Pengabdian masyarakat adalah meningkatkan pengetahuan masyarakat tentang Interaksi Sosial Orang Dengan Hiv/Aids (Odha) Dalam Mengurangi Stigma. Pelaksanaan pengabdian masyarakat dilakukan dengan melalui beberapa tahapan, yaitu tahap persiapan, tahap pelaksanaan, dan tahap evaluasi. Hasil pengabdian masyarakat menunjukkan Hubungan dari faktor sikap keluarga terhadap stigma ODHA signifikan dengan nilai p value 0.006. Pengabdian masyarakat dilakukan kepada 74 orang peserta dengan mayoritas berjenis kelamin perempuan usia di atas 45 tahun. Faktor yang memengaruhi stigma terhadap ODHA di Kelurahan Cipondoh adalah sikap keluarga terhadap ODHA dan persepsi responden terhadap ODHA. Perlu pemberian informasi HIV/AIDS yang lengkap kepada masyarakat untuk memberikan pemahaman yang dapat mengubah persepsi individu dan masyarakat termasuk keluarga, tetangga, dan tokoh masyarakat tentang ODHA.